The Influence of Canva-Supported Genre-Based Approach on Students' Narrative Text Writing Ability - Dea Irenia; Dyah Aminatun (Universitas Islam Negeri Palopo, 2025)
Writing skill plays a crucial role in English language learning, yet many students still face challenges in producing narrative texts, particularly in terms of organization, language use, and creativity. This study involved 68 eleventh-grade students and investigated the influence of the Canva-supported Genre-Based Approach (GBA) on their ability to write narrative texts at SMA Negeri 16 Bandar Lampung. Using a quasi-experimental design with pre-test and post-test control groups, the experimental group received instruction through the Canva-supported GBA, while the control group was taught using traditional methods, characterized by teacher-centered explanations, textbook-based writing exercises, and minimal use of digital media or interactive learning activities. Data were collected through writing assessments and questionnaires. Results revealed that the experimental group outperformed the control group significantly (p < 0.001; Cohen’s d = 2.55). Moreover, 85% of students agreed that Canva enhanced their creativity and motivation in writing. These findings highlight the value of integrating digital tools such as Canva into writing lessons to promote more engaging and effective EFL classrooms.